Study of impurity in blue spinel from the Luc Yen mining area, Yen Bai province, Vietnam - Huong, Le Thi Thu; Haeger, Tobias; Phan, The-Long (Vietnam Journal of Earth Sciences, 2018)
In this paper, we present the main impurities in natural blue spinel from the Luc Yen mining area in Yen Bai province, Vietnam. Together with identifying impurities and their valence, we have taken into account the site of some impurities in the MgAl2O4 spinel structure by using sensitive techniques, including Electron Microprobe Analysis (EMPA), UV-Vis-NIR, electron spin resonance (ESR), and X-ray absorption (XAS). EMPA results indicated that blue spinel contains different impurities, including V, Mn, Ni, Zn, Ti, Cr, Fe, Co and Ca. UV-Vis-NIR, ESR and XAS studies revealed that the oxidation state of Mn, Co, Fe and Ni is 2+ while that of Cr is 3+. Particularly, Co2+, Fe2+, and Cr3+ ions are identified to contribute to color variation in the blue spinel samples. Our study also indicated Co2+ and Cr3+ located in the octahedral position of Al3+ of the MgAl2O4 structure.References D'Ippolito V., Andreozzi G.B., Hålenius U., Skogby H., Hametner K., Günther D., 2015. Color mechanisms in spinel: cobalt and iron interplay for the blue color. Physics and Chemistry of Minerals, 42, 431-439. Chauviré B., Rondeau B., Fritsch E., Ressigeac P. and Devidal J.L., 2015. Blue spinel from the Luc Yen district of Vietnam, Gems & Gemology, 51, 2-17. Garnier V., Giuliani G., Ohnenstetter D., Fallick A.E., Dubessy J., Banks D., Vinh H.Q., L’homme T., Maluski H., Pêcher A., Bakhsh K.A., Long P.V., Trinh P.T., Schwarz D., 2008. Marble-hosted ruby deposits from Central and South-East Asia: Toward a new genetic model. Ore Geology Reviews, 34, 169-191. Gaft M., Reisfeld R., Panczer G., 2005. Modern luminescence spectroscopy of minerals and materials, Springer-Verlag Berlin Heidelberg, 96-97. Giuliani G., Dubessy J., Banks D., Vinh H.Q., Lhomme T., Pironon J., Garnier V., Trinh P.T., Long P.V., Ohnenstetter D., Schwarz D., 2003. CO2-H2S-COS-S8-AlO(OH)-bearing fluid inclusions in ruby from marble-hosted deposits in Luc Yen area, North Vietnam. Chemical Geology, 194, 167-185. Ikeya1 M., 1993. New Applications of Electron Spin Resonance, World Scientific Publishing, 34-57. Juhin A., G. Calas, D. Cabaret, L. Galoisy and J. L. Hazemann, 2007. Structural relaxation around substitutional Cr3+ in MgAl2O4. Physical Review B, 76, 54-105. Nguyen H.M., Dang N.V., Chuang P.Y, Thanh T.D., Hu C.W, Chen T.Y., Lam V.D., Lee C.H., Hong L.V., 2011. Tetragonal and hexagonal polymorphs of BaTi1-xFexO3- δ multiferroics using x-ray and Raman analyses. Applied Physics Letters, 99, 202-501. Leloup P.H., Arnaud N., Lacassin R., Kienast J.R., Harrison T.M., Trinh P.T., Replumaz A., Taponnier P., 2001. New constraints on the structure, thermochronology, and timing of the Ailo Shan-Red River shear zone, SE Asia. Journal of Geophysical Research, 106, 4, 6683-6732. Padlyak B.V., Grinberg M., Lukasiewicz T., Kisielewski J., Swirkowicz M., 2003. EPR spectroscopy of the Cr3+ centers in LLGG:Cr single crystals. Journal of Alloys Compounds, 361, 6-12. Shigley J. E. and Stockton C. M., 1984. Cobalt-blue gem spinels. Gems & Gemology, 20, 34-41. Teo B.K., 1986. EXAFS: Basic principles and data analysis, Springer-Verlag.